School Heads’ Leadership Traits and Learners’ Academic Attainment in Uganda’s High Schools - Naluwemba, Frances; Sekiwu, Denis; Tamale Kaggwa, Victoria (Donnish Journal of Educational Research and Reviews, 2015)
This paper analyses the correlation between School heads’ leadership traits and learners’ attainment in Uganda, with a sample of 12 secondary schools in Kampala Metropolitan City. The study findings were as such: High-performing schools register high student grades (μ=68. 47) compared to Moderately-performing schools (μ=58.2) and Low-performing schools (μ=37.41). Secondly, the situational leader is the most appropriate trait to account for improved academic attainment (F=18.41), followed by the democratic trait (F=17.06), the laissez faire management trait accounting for n F statistic of 10.39, and the autocratic school head (F=10.01). Third, the higher the situational leadership trait is used, the higher the learners’ academic attainment (β1=0.653; p≤0.05). Fourth, democratic trait school heads reasonably influence learners’ academic attainment (β2=-0.481; p≤0.05). Learners’ academic attainment is incompatible with autocratic trait school headships (β3=-0.651; p≤0.05), just as it is similar with laissez faire trait school heads (β4=-0.292; p≤0.05). Finally the study recommends that situational school headship is more appropriate for academic attainment because of being more adaptable to the current demands of the teaching service.
Keywords: Leadership styles; Head teachers‟ leadership; Academic achievement; Uganda's education